Targeting osteoarthritis with small extracellular vesicle therapy: potential and perspectives - González-Rodríguez, Alba; De Toro, F. Javier; Jorge-Mora, Alberto; Fernandez-Pernas, Pablo; Rivadulla, Carlota Probaos; Fraga, María; Fafián-Labora, Juan A.; Arufe, María C. (Frontiers in Bioengineering and Biotechnology, 2025)
Osteoarthritis (OA) is a degenerative joint disease marked by inflammation, cartilage degradation, and pain, leading to a significant decline in quality of life. Recent advancements in extracellular vesicle (EV) research have introduced new therapeutic possibilities, with small extracellular vesicles (sEV) emerging as a promising strategy for OA treatment. sEV, particularly those derived from mesenchymal stem cells (MSCs), synoviocytes, chondrocytes, and induced pluripotent stem cells (iPSCs), demonstrate substantial anti-inflammatory and regenerative properties. These nanosized vesicles facilitate intercellular communication, delivering bioactive molecules that can modulate the joint microenvironment, promote chondrogenesis, and alleviate pain. Preclinical and early clinical studies indicate that sEV-based therapies may slow disease progression and enhance cartilage repair in OA patients. Despite the promising potential, challenges remain, including standardizing isolation techniques, understanding underlying mechanisms, and navigating regulatory pathways. This systematic review analyzes relevant publications published between 2019 and 2025, highlighting the therapeutic and biomarker potential of sEV in OA. Although there is substantial ongoing research into sEV and biomarkers, the fundamental understanding of OA pathogenesis remains largely unchanged, with most studies continuing to focus on established mechanisms of cartilage degradation, inflammation, and subchondral bone changes. The findings suggest that while therapeutic research into sEV is progressing, advancements in unraveling new pathophysiological mechanisms of OA are more limited. Further research is essential to optimize therapeutic protocols and establish clinical efficacy, marking sEV-based therapies as a promising but evolving approach for OA treatment.